ROLE OF THE JUDICIARY AND THE LEGAL PROFESSION IN ENSURING THE RULE OF LAW: GLOBAL DIMENSION - Вільчик, Т.Б. (SWorldJournal, 2025)
The article is devoted to analyzing the key role of the judiciary and the legal profession in ensuring the rule of law in the modern world. It highlights the importance of the independence of judges and lawyers as effective mechanisms for access to justic